Exploring the Evolution and Diverse Applications of Immobilized Glucose Oxidase: A Comprehensive Review - G. Sreenivasulu; R.Ramakoteswara Rao (Advances in Engineering and Intelligence Systems)
The glucose oxidase enzyme (GOx), also known as notatin (EC number 1.1.3.4), functions as an oxidoreductase that facilitates the oxidation of glucose to hydrogen peroxide and D-glucono-δ-lactone. This lactone then spontaneously converts to gluconic acid while concurrently generating hydrogen peroxide. The widespread applications of glucose oxidase have garnered significant attention across diverse industries such as chemical, pharmaceutical, food and beverage, clinical chemistry, biotechnology, and others. This enzyme is naturally produced by certain species of fungi and insects and exhibits antibacterial properties in the presence of oxygen and glucose. As the demand for glucose oxidase continues to rise and its production remains limited and costly, the reuse of enzymes becomes crucial. Moreover, when the enzymes are immobilized on suitable surfaces, their activity tends to increase. Immobilization refers to the process of attaching enzymes to surfaces, and various methods exist for achieving this immobilization. The choice of a specific immobilization method depends on factors such as the intended application, cost, activity, reproducibility, and half-life. This review provides a comprehensive overview of the principles and methods of enzyme immobilization in general and specifically focuses on a chronological survey of immobilized glucose oxidase. It further discusses the objectives and applications associated with this field.